A review of the soft side in project management: concept, trends and challenges - Cardoso dos Santos Durão, Luiz Fernando; Di Favari Grotti, Marcelo Vinicius; Minetto Maceta, Paulo Rafael; Zancul, Eduardo; Berssaneti, Fernando; Monteiro de Carvalho, Marly (Revista Gestão da Produção Operações e Sistemas, 2017)
Our aim is to analyze the changes that have taken place in the academic literature of project management induced by the growing interest in the soft side within project management, identifying concepts, trends and challenges. Based on a bibliometric approach, a systematic literature review focusing on content analysis was made in articles published from 1994 to 2015 in the ISI Web of Science and Scopus databases. The literature was found to maintain the separation between the hard and the soft side, being the soft side, for most researchers, an enabler of project performance and success. Each kind of examined skills provides different aspects of project quality and management, being the hard side clearer and more objective and the soft side more ambiguous and subjective. In the whole article, the base used 13 soft skills. The most cited among them was ‘Communication’, cited fifteen times, followed by ‘Leadership’ and ‘Teamwork’ cited nine times each. Despite the stronger impact of the soft skills in the project performance, the literature says that the project members, within the project team, must combine soft and hard skills towards the best performance of the projects.